Inventory of Medicinal Plants Used by the Community of Rano Village, Balaesang Tanjung District, and Their Potential as Biology Learning Media - Nunink; I Nengah Kundera; I Made Budiarsa; Musdalifah Nurdin; Vita Indri Febriani; Masrianih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aims to inventory the plant species utilized by the local community as medicinal resources in Rano Village, Balaesang Tanjung Sub-district, and to examine their potential use as instructional learning media. The study employed a descriptive research design with a qualitative approach. Primary data were collected directly through interviews and field observations using a survey method with purposive sampling. Data collection techniques included direct observation, community interviews, and documentation of field findings. In the local context, a traditional healer (sando) plays a significant role as a key informant due to their extensive knowledge regarding the identification and use of medicinal plants. The results of the study revealed that the community utilizes 22 species of medicinal plants belonging to 14 plant families to treat various ailments, including rheumatism, asthma, hypertension, itching, scabies, cough, influenza, and several other health conditions. The plant parts used include leaves, stems, fruits, roots, bark, shoots, sap, and in some cases the entire plant. The preparation and utilization methods commonly practiced by the community include pounding, boiling, topical application, and direct consumption. Based on these findings, the documented information on medicinal plant utilization has strong potential to be developed as instructional media in the form of an educational e-book to support biology learning.